Wheat Yield, Biomass, and Radiation Interception and Utilization Under Conservation Tillage: Greater Response to Drip Fertigation Compared to Intensive Tillage - Yuechao Wang; Jinxiao Song; Wen Li; Tingting Yan; Depeng Wang; Jianfu Xue; Zhiqiang Gao (Agronomy)
Conservation tillage, particularly no tillage (NT), has been recognized as an efficient farming practice, particularly in dryland agriculture, as it significantly enhances crop yields, improves soil health, and contributes to environmental sustainability. However, the influence of NT on winter wheat radiation interception and utilization, biomass, and yield under NT in irrigated fields, especially under drip fertigation, is unclear. A field experiment was carried out for two growing seasons in Shandong province, China, using a split-plot design with the tillage method as the main plot (no tillage, NT; rotary tillage, RT; and first plowing the soil and then conducting rotary tillage, PRT), and water–nitrogen management as the sub-plot (N fertilizer broadcasting and flood irrigation, BF and drip fertigation, DF). Our results showed that DF increased yield by 11.0–28.5%, but the yield response to DF depended on the tillage methods. NT had the highest response in yield of 26.3–28.5%, followed by RT of 14.6–15.1% and PRT of 11.0–11.9%. Both increased grains per ear and ear number, a result of the greater maximum stems number donating to the yield gain by DF under NT. This gain was also due to the substantially promoted post-anthesis biomass (36.7–47.3%), which resulted from the increased interception of solar radiation and radiation use efficiency after anthesis. In addition, the extended post-anthesis duration also benefited biomass and yield. To conclude, our findings underscore the critical need to optimize water and nitrogen management strategies to maximize yield under conservation tillage systems.